Landscape planning as an instrument for environmental quality management of urban areas - Клєщ, Анастасія Анатоліївна (Technology audit and production reserves, 2014)
This article discusses the need in landscape planning in the management of environmental quality in urban areas and some results of the author’s research in this area. The main objective of the study is to find ways to improve the effectiveness of environmental management of urban areas by means of landscape planning methods and principles. By using the methodological framework of landscape planning in research it is possible to identify the scenarios of its development based on a comprehensive spatial analysis of the study area. This article discusses the results of the inventory phase of landscape planning on the example of Dzerzhinsky district of Kharkiv. The developed models are digital map information resource basis to support management decision-making in the field of environmental protection. The research results can be used to developing a system of environmental protection measures, as well as integrated landscape planning of Kharkiv.